A methodological approach in order to support decision-makers when defining Mobility and Transportation Politics - José Manuel Viegas; Miguel Gaspar; Elisabete A. Silva (European Regional Science Association (ERSA), 2004)
Nowadays Portugal is under a large process of creation/revision of studies and plans related with land use and territorial planning, mainly due to the end of the lifetime period of the actual Municipal Master Plan, but also because of the creation of the new Metropolitan Authorities of Transportation, which will require Mobility Plans. Even though the Portuguese law doesn't impose these Mobility Plans at the present moment, there is a general feeling about the importance of the mobility system for the society and economics in general. This is the case in highly density areas, where the need and complexity of the system requires these specific studies in order to obtain an efficient management; or in the case of low-density areas where the risk of loosing competitiveness is too high to ignore the importance of the transportation and mobility system, and the advantage of gaining local and regional competitiveness might increase the importance of the municipality in regional context. This paper intends to provide an innovative approach regarding the provision, at an early stage, of technical support to decision-makers in order to define Mobility and Transportation Policies. The opportunity provided by using adapted SWOT analysis (among others) to identify weakening or potential factors, and how to take advantage of the results, always using a cause and effect approach and a coherent policy in order to obtain high quality and effective studies and politics. The methodology relies on a two-stage process. In the first stage a summary diagnose is provided, using inputs which are supposed to well characterise the territory's mobility patterns. Afterwards, in a second phase, these are inter-related and evaluated in order to build-up a table of options, where policies are proposed with a careful attention to its qualitative cross impact with the measures and objectives intended to be achieved. The proposed methodology was applied in the Alcobaça's Municipality case study, which provided different lines of action in diverse subjects, such as, public and private transportation networks, parking policies and organisation, and territory competitiveness. This study was particularly relevant, since this Municipality is under great pressure of its neighbour municipalities, has a low level of regional importance and a low intra-municipal cohesion. Finally, the general opinion of the decision-makers about this technical approach is presented. Keywords: Mobility; Transportation; Land Planning and Policies; Decision-making Support
Keywords: 330; Mobility; Transportation; Land Planning and Policies; Decision-making Support